Electroconvulsive Therapy and Its Association With Demographic and Clinical Characteristics in Chinese Psychiatric Patients. Issue 2 (June 2015) - Wang, Zhi-Min; Zhu, Hui; Pan, Yan-Li; Chiu, Helen F. K.; Correll, Christoph U.; Ungvari, Gabor S.; Lai, Kelly Y. C.; Cao, Xiao-Lan; Li, Yan; Zhong, Bao-Liang; Zhang, Xiang-Yang; Xiang, Yu-Tao
Abstract : Purpose: Little is known about the frequency of electroconvulsive therapy (ECT) use in China. This study examined the frequency of ECT and its relationship with demographic and clinical characteristics in a large psychiatric institution in China. Methods: This was a retrospective chart review of all the 19, 982 inpatients aged 18 to 59 years treated during the period of 8 years (2007–2013) in a tertiary psychiatric institution in Beijing. Sociodemographic and clinical data were collected from the electronic chart management system for discharged patients. Results: The frequency of ECT use was 57.7% in the whole sample, 68.4% in bipolar disorders, 66.3% in major depression, 55.2% in schizophrenia, and 28.6% in other psychiatric disorders. Patients who received ECT (ECT group) had shorter length of hospitalization compared with the non-ECT group. In multiple logistic regression analysis, ECT use was independently associated with age younger than 30 years; higher risk for suicide and aggression at time of admission; mood disorders; lower risk for falls; more treatment with antipsychotics, mood stabilizers, and antidepressants; less health insurance coverage and major medical conditions; as well as non–local residency status. Compared with 2007 (35.5%), ECT use significantly increased in the period of 2008 (49.1%) to 2013 (61.9%). All these significant correlates combined explained 20% of the variance of ECT use ( P < 0.001). Conclusions: In a major psychiatric center in China, the use of ECT was much more common than the figures reported from most countries around the world. Reasons for this difference and variances in outcomes between settings with higher and lower ECT use should be studied.